Gene expression of sirtuin-1 in adult with hypertension - Yohana, Yohana; Faradilla, Meutia Atika; Tungka, Endrico Xavierees; Kurniasari, Kurniasari (STKIP Persada Khatulistiwa Sintang, 2025)
SIRT1 is a key member of the sirtuin family, exerts a unique protective effect on endothelial cells by modulating various proteins, and has a role as an anti-aging biomarker. Hypertension is pathology chronic pathological condition that disrupts ROS and antioxidants. Little evidence showed that sirtuin has a role in chronic oxidative stress. Therefore, the objective of this study was to analyze the relative expression of Sirtuin-1 in hypertension. This is a case-control study with 30 subjects, adults 50-60 years old in each group. JNC 8 was used to determine blood pressure. Quantitative Real Time PCR was used to calculate the level of Sirt-1. The Livak method was used for relative expression. JASP software was used for data analysis. Our study showed Sirtuin-1 mRNA expression was significantly lower in the hypertension group than the normotension group. It was 0.52 fold lower in hypertension. Sirtuin-1 stimulates antioxidants such as superoxide dismutase and catalase through FOXO-dependent signaling. It has a similar role to antioxidants for eliminating ROS. Sirtuin-1 expression is significantly reduced in individuals with hypertension, suggesting its potential role in oxidative stress regulation and its value as a biomarker for vascular aging and hypertension-related endothelial dysfunction.Keyword: Sirtuin-1, hypertension, expression, mRNA